Freud's psychoanalysis of religion - Garvey, Brian P. (Trinity College (Dublin, Ireland). Philosophy Department, 2000)
Freud was part of a long tradition of non-believers who offered a story about how religions originated. Notable works in this tradition include Hume's The Natural History of Religion and Feuerbach's The Essence of Christianity. Such works typically fulfil one or more of the following three functions : (1) To rebut the claim, sometimes made by religious apologists, that the fact of religion existing, and being as widespread as it is, cannot be explained in purely naturalistic terms, and therefore requires an explanation which invokes supernatural entities. I call this the counterapologetic aim. (2) To discover, just as an end in itself, the truth about how religions originated. I call this the historical aim. (3) To persuade readers to abandon religion without fear that the quality of their life will suffer thereby. I call this the therapeutic aim.
Keywords: Philosophy, Ph.D.; Ph.D. Trinity College Dublin